Outcomes following aortic valve replacement for isolated aortic stenosis with left ventricular dysfunction - Naicker, A; Brown, S; Ponnusamy, S (SA Heart Journal, 2017)
Background: Severe aortic stenosis (AS) is associated with a poor prognosis in patients with left ventricular dysfunction (LVD). Survival is estimated at less than 2 years without aortic valve replacement (AVR). Limited data are available on the effects and outcomes of AVR in such patients, especially in the absence of concomitant coronary artery disease (CAD). Methods: This was a retrospective study which identified 33 patients over an approximate 10 year period who underwent surgical AVR for severe isolated AS and LVD(LVEF ≤50%). Patients were excluded if they had a prior valve replacement, mixed valve disease, <18 years old or the presence of CAD. Overall survival was analysed using the Kaplan-Meier curve and Cox proportional hazards model. The changes in postoperative LVEF and NYHA functional class, following AVR, was assessed using the Friedman test and ANOVA. Results: Operative mortality was 15% with 5 deaths. Female sex and hyperlipidaemia were identifi ed as predictors of early mortality by univariate analysis. LVEF improved in survivors from a mean of 39 ± 10% - 49.8 ± 8.7% at a 1 year follow-up (p=0.04). Younger age was identifi ed as an independent predictor of LVEF recovery (p=0.04). There was no difference in outcomes in patients with low baseline transvalvular gradients compared to those with higher gradients. There was signifi cant symptomatic improvement noted in all survivors following AVR (p<0.01). Conclusion: Left ventricular function has a slower rate of recovery, compared to an earlier improvement of NYHA functional class after AVR for severe isolated AS and pre-operative LVD. In this high-risk group the fi ndings support AVR in patients with LVD.